Activation of the Wnt signaling pathway and its role in epithelial-mesenchymal transition and hepatic fibrosis in alveolar echinococcosis - Wu, Binjie; Yang, Yuxuan; Cheng, Shilei; Wang, Zhixin; Fan, Haining (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveThis study examined the effects of Echinococcus multilocularis infection on the activation of the Wnt signaling pathway in hepatocytes, its association with epithelial-mesenchymal transition (EMT), and its role in E. multilocularis-induced hepatic fibrosis.MethodsHepatic lesion tissues were obtained from 20 patients with clinically diagnosed alveolar echinococcosis (AE). These tissues were categorized into near-lesion and distant-from-lesion groups. Additionally, a murine model of AE infection was developed through the injection of E. multilocularis protoscoleces. The mice were divided into control, Wnt pathway enhancement (Wnt3a), and Wnt pathway inhibition (DKK1) groups. Four weeks post-infection, AAV-EGFP, AAV-Wnt3a-EGFP, or AAV-DKK1-EGFP vectors were administered, followed by tissue collection four weeks later. Both human and murine liver tissues were analyzed using Masson’s trichrome, hematoxylin and eosin (H&E), and Sirius red staining, as well as immunohistochemical and western blot analyses to assess protein expression levels associated with EMT and fibrosis.ResultsElevated expression levels of Wnt3a, β-catenin, N-cadherin, Col1a1, α-SMA, Vimentin, CTGF, and TGF-β were observed in tissues adjacent to human AE lesions and in the Wnt3a-treated mouse group. Conversely, E-cadherin expression was low. Immunohistochemical analysis demonstrated lower expression of Wnt3a, β-catenin, and other EMT- and fibrosis-related proteins in perilesional areas in human tissues and in the DKK1-treated mouse group, while increased E-cadherin expression was elevated. Inflammatory cell infiltration and fibrosis were observed near human lesions, whereas the DKK1-treated mouse group exhibited significantly reduced fibrosis.ConclusionThe Wnt signaling pathway plays a key role in the development of hepatic fibrosis associated with AE infection. Its activation is positively correlated with EMT and the increased expression of fibrogenic markers, including Collagen I, CTGF, and TGF-β, thereby contributing to the progression of hepatic fibrosis in hepatic AE.